Polymerization of Thienothiophenes and Dithienothiophenes via Click-Reaction for Electronic Applications - EROĞLU, MEHMET SAYIP (WILEY-V C H VERLAG GMBH, 2016)
In this work, donor acceptor (D - A) copolymers of thienothiophenes and dithienothiophenes, having 1,2,3-triazole units were prepared via a click reaction. Their optoelectronic properties were explored systematically providing the optical and electrochemical band gaps varying from 2.2 to 2.8 eV. Density functional theory (DFT) investigations of the model compounds revealed the presence of an intramolecular charge transfer transition between the donor TT/DTT units and 1,2,3-triazole acceptor group.
Keywords: Thienothiophene; Dithienothiophene; Click reaction; Optoelectronic property; DFT; POLYMERS; DENSITY; TRANSISTORS; CHEMISTRY; OLIGOMERS; ENERGIES; DONOR; MODEL